Classics education in Northern Irish primary schools; curriculum policy and classroom practice - Amber Taylor; Arlene Holmes-Henderson; Sharon Jones (The Journal of Classics Teaching, 2023)
This study explores the perspectives of teachers and pupils regarding the benefits and challenges of teaching Classics in primary classrooms in Northern Ireland (NI). Conducted in 2020, the methodological approach consisted of interviews with six teachers from three schools and a focus group held with eight children.1 The study identified positive impacts of teaching Classics on numerous subjects, including Modern Foreign Languages (MFL). The most pressing challenge appeared to be a crowded curriculum. Teachers and pupils suggested that training and support be offered to educators in order to optimise links between Latin, English literacy and MFL understanding. Finally, recommendations are made for the future study of Classics in Northern Ireland.